2021
DOI: 10.3390/safety7020026
|View full text |Cite
|
Sign up to set email alerts
|

Older Drivers’ Motion and Simulator Sickness before and after Automated Vehicle Exposure

Abstract: Older drivers desire independence in mobility, and automated vehicles hold plausible opportunities to realize this goal. Motion sickness (automated shuttle exposure) or simulator sickness (automated driving simulator exposure) may affect acceptance of these technologies. This study investigated the onset of motion and simulator sickness in older drivers (mean age = 74.29, SD = 5.96; female = 54%) after exposure to an automated shuttle and automated driving simulator and assessed age and sex as determinants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…To prevent, minimize, or mitigate the occurrence of simulator sickness, we implemented a standardized simulator sickness protocol as detailed in the study [38]. The research team offered dietary recommendations to participants prior to their participation in the driving simulator experiment, ensured a comfortable temperature-controlled environment (72℉), provided a 5-min acclamation period prior to the start of actual simulation ride, and used a Motion Sickness Assessment Questionnaire (MSAQ) for subjects to self-report symptoms of sweatiness, queasiness, dizziness, and nauseousness.…”
Section: Methodsmentioning
confidence: 99%
“…To prevent, minimize, or mitigate the occurrence of simulator sickness, we implemented a standardized simulator sickness protocol as detailed in the study [38]. The research team offered dietary recommendations to participants prior to their participation in the driving simulator experiment, ensured a comfortable temperature-controlled environment (72℉), provided a 5-min acclamation period prior to the start of actual simulation ride, and used a Motion Sickness Assessment Questionnaire (MSAQ) for subjects to self-report symptoms of sweatiness, queasiness, dizziness, and nauseousness.…”
Section: Methodsmentioning
confidence: 99%
“…Half of the participants completed a 5 min acclimation scenario via random allocation (i.e., randomization using randomizer.org). The associations between participants’ simulator sickness provocation, age, and gender are detailed in a separate paper ( 30 ). Each participant was seated in the driver’s seat and asked to “put the vehicle in drive and press the on button.” The scenario lasted 10 min and occurred at low-to-moderate speed (15–35 mph) in a suburban environment with the autonomous system handling all driving tasks.…”
Section: Methodsmentioning
confidence: 99%
“…With regards to biological sex, it has been repeatedly reported that females experience motion sickness and VIMS more frequently and more severely than men in self-reported surveys [5 ▪▪ ,27,28] as well as in laboratory studies [29 ▪ ,30]. However, it is noteworthy that some experimental studies failed to find differences in motion sickness/VIMS between women and men [4,31], questioning the robustness of this effect. The reason for a potential sex-related difference in motion sickness/VIMS susceptibility remains speculative.…”
Section: Influencing Factors and Individual Susceptibilitymentioning
confidence: 99%
“…Two current trends make motion sickness a topical issue: First, the era of automated vehicles has begun, and it is expected that fully automated vehicles will eventually be on our roads. However, the risk of motion sickness is significantly increased in automated vehicles as the motion of the vehicle can no longer be controlled [3,4]. Although drivers are far less affected, about 46% of the adult population experience motion sickness as passengers in cars, making it a serious concern for the development of automated vehicles [5 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%